DOMINANT FACTORS AFFECTING CAPITAL REALIZATION IN SOUTHEAST SULAWESI - Muhamad Armawaddin; Ahmad Ahmad (Jurnal Ekonomi Pembangunan, 2018)
This study aims to determine the dominant factors that affect the realization of capital expenditure in districts/cities in Southeast Sulawesi. This type of data used is secondary data on local revenue, equity funds, personnel expenditures, gross regional domestic product, residual funding, population and capital expenditures during 2010-2016. The analysis uses regression analysis of panel data from 12 districts / cities by Ordinary Least Square (OLS) method. The result of the research shows that the dominant factors affecting capital expenditure realization is balance fund. The other result is PAD, personnel expenditure, GRDP which have a significant effect on capital expenditure realization, while the population is not significant. SILPA has significant effect to capital expenditure with partial regression test but not significant with multiple regression test.